(untitled) (American International Journal of Economics and Finance Research, 2020)
This study examined the effect of monetary policy on assets quality indicator of Nigeria commercial bank soundness from 2009 to 2018. Cross sectional data were sourced from annual reports of commercial banks and Central Bank of Nigeria Statistical Bulletin. Assets quality indicator of commercial banks soundness was used as proxies for the dependent variables while cash reserve ratios, open market operation rates, monetary policy rates, treasury bills rates and money supply were used as proxies for the independent variables. Panel data methodology was employed while the fixed effects model was used as estimation technique at 5% level of significance. Fixed effects, random effects and pooled estimates were tested while the Hausman test was used to determine the best fit. Panel unit roots and panel cointegration analysis were conducted on the study. Findings of the study proved that cash reserve ratio, open market operations rates, monetary policy rates and treasury bills rates have no significant relationship with assets quality indicators of commercial banks in Nigeria. However, Money supply has significant relationship with assets quality indicators of commercial bank soundness in Nigeria. From the findings we recommend that Central Bank of Nigeria should intensify the use money supply as a veritable effective monetary policy tool to achieve bank soundness in Nigeria. Furthermore, CBN should redefine these monetary policy instruments such as open market operation and adjust the monetary policy rate by reducing the cash reserve ratio which will increase liquidity to enable the commercial banks to discharge their lending and investment duties effectively to the public. The cash reserve ratio should be used to complement the open market operations in ensuring that excess liquidity or lack of it in the banking system is minimized. It was further recommended that CBN should look beyond monetary policy in her regulatory governance of commercial banks as most monetary policy tools currently deployed do not have significant relationship with commercial bank soundness indicators within the periods covered in this study.